Shakespeare in Asia contemporary performance - Kennedy, Dennis 1940-; Yong, Li Lan (Cambridge University Press, 2010)
"The aim of this collection is to expand theoretical and functional discussion about the condition and significance of Shakespeare performance in contemporary Asia. As we explain in the introduction, we do not pretend to a comprehensive view of the topic, or allot an equivalent number of essays to competing regions, or suggest that our examples are necessarily representative of national or international trends. Any such approaches would distort the topic, given the size of Asia and the diversity of approaches to Shakespeare and performance found there. Instead we have tried to focus attention on why Shakespeare has been of use in an area of the world that has no inherent reason to call on him, investigating some of the ways his work has been reinvented and deployed"--Provided by publisher.